Effects of gamma irradiation on chickpea seeds vis-a-vis total seed storage proteins, antioxidant activity and protein profiling - Bhagyawant, S S; Gupta, N; Shrivastava, N (Cellular and Molecular Biology, 2015)
The present work describes radiation-induced effects on seed composition vis-í -vis total seed proteins, antioxidant levels and protein profiling employing two dimensional gel electrophoresis (2D-GE) in kabuli and desi chickpea varities. Seeds were exposed to the radiation doses of 1,2,3,4 and 5 kGy. The total protein concentrations decreased and antioxidant levels were increased with increasing dose compared to control seed samples. Radiation induced effects were dose dependent to these seed parameters while it showed tolerance to 1 kGy dose. Increase in the dose was complimented with increase in antioxidant levels, like 5 kGy enhanced % scavenging activities in all the seed extracts. Precisely, the investigations reflected that the dose range from 2 to 5 kGy was effective for total seed storage proteins, as depicted quantitatively and qualitative 2D-GE means enhance antioxidant activities in vitro.